The village government’s communication model: A promotion strategy for stunting prevention in Indonesia - Nur, A Fahira; Suriati; Nur, Makmur Jaya; Arifuddin, Adhar; Rahman, Nurdin; Fajriah, Rasyika Nurul; Wahyuni, Rosa Dwi (YCAB Publisher, 2023)
Background: Stunting remains a significant social issue among the population in Indonesia. Inadequate treatment has led to numerous cases of suboptimal height in children aged 19 years. Objective: This study aimed to explore the strategy of the village government in formulating communication messages, utilizing communication methods, and employing communication media for the stunting alleviation program. Methods: A phenomenological approach was employed, with the research conducted in Pulau Harapan Village, Nine Island District, Sinjai Regency. Data were gathered from the government officials of Pulau Harapan Village through observations, interviews, and documentation. Subsequently, the collected data underwent analysis involving reduction, presentation, verification, and conclusions drawing, facilitated by Atlas TI 8 software. Results: The village government's strategy in crafting stunting alleviation program messages, from socialization to implementation in Harapan Island Village, Nine Island District, Sinjai Regency, revolves around the Two-Step Flow Communication model. The communication methods used include information repetition, channelization, persuasion to alter the target mothers' perceptions, educational methods, and coercion (coerfindings). Media employed include print media, electronic media, and human resource mobilization within Harapan Island Village. Conclusion: The findings of the study provide valuable insights to address the stunting issue in Indonesia.